Non-constancy of the bulk resistance of ionophore-based Cd2+-selective electrode: A correlation with the water uptake by the electrode membrane. (20th February 2020) - Kalinichev, Andrey V.; Solovyeva, Elena V.; Ivanova, Arina R.; Khripoun, Galina A.; Mikhelson, Konstantin N.
Abstract: The dependence of the bulk resistance of Ion-selective electrodes (ISEs) on the concentration of aqueous solution is studied by means of chronopotentiometry and electrochemical impedance using Cd 2+ -ISE as model system. It is shown that within the Nernstian response range that bulk resistance of the ISE membrane increases along the dilution of the aqueous phase. The results are consistent with analogous studies carried out earlier with Ca 2+, K + and NO3 − -ISEs. Water uptake by the Cd 2+ -ISE membrane is studied systematically, and it is shown that the water uptake also increases along decrease of the concentration of CdCl2 solution. The shapes of the concentration dependence of the two properties: (1) the membrane bulk resistance and (2) the water uptake, are very similar, suggesting a correlation between (1) and (2). SEM/EDX studies of Cd 2+ -ISE membranes confirm uniform distribution of the components within dry membranes, except of surface layers which are enriched in plasticizer and depleted in the polymer. It is concluded that the ISE membranes equilibrated with aqueous solutions must be considered as non-homogeneous materials due to the presence of the dispersed water. It is assumed that the electrochemical equilibrium is established between the solution and the membrane organic phase proper, while the resistance refers to the membrane as a material including water droplets which hinder the charge transfer across the membranes. Graphical abstract: Image 1 Highlights: Bulk resistance of ionophore-based membranes varies over the Nernstian response range. Water uptake by the membranes increases over dilution of the aqueous phase. The bulk resistance correlates with the water uptake. Because of the water uptake the membranes are essentially heterogeneous. Advanced theory must consider heterogeneity of the membranes.